Quality Assessment of Underground Water Resources in the Northeast of Sabzevar - Fazel Valipour, Mohammad Ibrahim; Erfanian Kaseb, Hengameh (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Introduction. In semi- arid and arid countries in which groundwaters are the main supplier of water, monitoring of water quality is of vital significance. To better manage water resources, therefore, investigation of water quality utilized for drinking, agricultural and industrial purposes sounds compulsory. The purpose of article. The aim of this study was to investigation the factors in fluencing the evolutionary process of groundwater resources and hydrogeochemical characteristics of groundwater resources in the northeast of Sabzevar. The research methods. Given the geological formation, water yield and condition of the region’s water resources, a total of 10 underground water resources were surveyed in respect of quality. In this regard, physical parameters e.g. PH, Electric Conductivity (EC) and Total Dissolved Solids (TDS) were measured in the sampled solution by multimeter. The hydrochemical analysis of data was implemented in laboratory and by inductive Plasma method and by statistical analysis and the modeling process were conducted by the SPSS, Chemistry and AqQA suites. The results of research. According to Scholler diagram, that most of water samples are categorized in good and acceptable class. According to the drawn Wilcox diagram, the samples are in C2S2, C2S4, C3S2 and C3S4 classes. Most samples agriculturally unsuitable with high salinity. According to the water quality index (GQI)), the water resources of the study area are in poor to acceptable category. Spatial study showed that the catchment area of water resources located in volcanic rocks, conglomerates and gravels, due to the lower impact of these rocks on water salinity, has caused the outflow of water of appropriate quality from these areas. In the western part of the region, due to the presence of marl and evaporation -detrital deposits, the value of this index is low and water is of poor quality. In other parts of the region, the water quality index (GQI), increases and water has a better quality. The type of geological formation around the basin is one of the important factors in the evolution of water resources. Chemical weathering of different rocks with natural waters produces different cations and anions. The water-rock reaction and weathering of minerals, is the main factor in changing the quality of groundwater chemistry in the region. Chemical analysis of water entering the aquifer of region showed that the sources of ions entering the region were affected by the lithology of rocks and sediments that were exposed to weathering for a long time, hence, as the region water, due to the passage of the detrital evaporation formation of the third period and marl, have dissolved them and increased the ratio of Cl+SO4>HCO3. The results showed that the presence of rocks and minerals of carbonate such as limestone, dolomite and calcite, sandstone and silicate such as volcanic rocks in the water passage has caused the scenarios of Ca>CO3 and Ca + Mg>CO3. Conclusions. Results revealed that drinking water resources are decent in most of the sites, exclusive of the resources that place in detrital-evaporate deposits. Meanwhile, the water is hypersaline and indecent for agricultural purpose. To the east, however, salinity plummets and is decent for agricultural purpose. The concentration of bicarbonate as the most abundant onion in the entire resources is higher than the global health standard and dissolution of carbonate rocks like limestones and dolomites play a role in this manner. The concentration of nitrate in the entire resources is lower than the global standard. Their concentration in the area is owing to agricultural activities and circulated water. Water resources emplaced in volcanics, conglomerate and gravels are of less concentration in respect of salts content and quality of water is higher. The young detrital-evaporate deposits in the west have augmented the concentration of ions as per the Ground Quality Index (GQI) and zonation maps, and where upon, water quality in this portion is poor.